Health-seeking behaviours of filipinos with common skin diseases - Dofitas, Belen Lardizabal
Skin ailments are often perceived as minor and non-life threatening but these disorders are highly prevalent, often visible, and can be produce significant discomforts and disability. Social stigma and economic difficulties bring more problems to the patient than the skin disease itself. For example, leprosy is still higly stigmatizing despite effective cures. Recently, the economic burden of 21 priority skin diseases in the USA was estimated at $37 billion annually. Based on economic surveys, an estimated 30-96% of Filipinos have dermatological problems. among the most common dermatoses, superficial fungal infections and excemas are considered the top priority conditions by dermatologists in the Philippines. The most common skin disorder among Filipinos is tinea versicolor (pityriasis versicolor), more popularly known as "an-an". It is superficial fungal infection that is quite benign but often disturbing because of its recurrent nature and cosmetically undersirable hypopigmentation among dar-skinned individuals. Tinea corporis (ringworm) and tinea pedis (athlete's foot) are the most common superficial fungal infections caused by dermatophytes. These are pruritic, inflamed, or dry and scaly. Eczemas are a group of inflammatory skin disorders, the most common of which are contact dermatitis, atopic dermatitis, and lichen simplex chronicus among Filipinos. Knowing health-seeking and coping behaviors that are specific to a group of skin diseases and to skin disease in general would be helpful for health program planners and affected persons. Health planners can tailor their promotional and service activities according to the needs of the patients with specific disorders. Persons who are afflicted with specific skin disorder can learn to practice proper self-care. promoting proper self-care increases the responsibility for one's own health and decreases dependence on health providers. Even small increases in appropriate self-care would likely lead to millions in health pesos saved.